Impact of Parental Involvement on Students’ Reading Proficiency - Pada, Judee Rose (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to determine the extent of parental involvement in the development of reading proficiency among Grade 7 students. Utilizing a descriptive-correlational research design, the study employed systematic sampling to identify 280 parents of Grade 7 students from 11 secondary public schools in the Sibulan 1 and 2 Districts, Division of Negros Oriental. Data collection was facilitated through the Philippine Informal Reading Inventory (Phil IRI) Assessment Tool and a validated questionnaire. Statistical analyses included percent, weighted mean, mean, and multiple regression analysis. The findings indicated that parental involvement in parenting was "high," while involvement in communicating, volunteering, learning at home, and decision-making was "somewhat high." The results showed that students' word reading scores were at the "instructional" level, whereas their comprehension scores were at the "frustration" level. Additionally, the study identified parenting as the only significant predictor of students' word reading and comprehension scores. Furthermore, student characteristics such as sex, age, and school location significantly predicted word reading scores, with female, younger, and urban-based students performing better. These findings underscore the critical role of parental involvement, particularly in parenting, in enhancing students' reading proficiency. The study suggests that targeted interventions to increase parental engagement in various forms could potentially improve reading outcomes for Grade 7 students.